Introducing the Euro as Legal Tender-Benefits and Costs of Eurorization for Cape Verde - Imam, Patrick (IMF Working Papers; Working Paper ;, 2009)
In recent years, recommendations for countries to unilaterally dollarize/eurorize have become common, particularly when the countries lack economic credibility. After exploring the characteristics of dollarizing/eurorizing economies, we look at the merits and costs of unilateral eurorization for Cape Verde, a highly tourism based economy that has become increasingly integrated into the euro-zone area and that has a strong macroeconomic track record. We illustrate that neither the benefits nor the costs of unilateral eurorization are large and conclude that there is no compelling case to change the current exchange rate arrangement at this point in time. Econometrically, we assess the characteristics of dollarized economies and demonstrate that few of them apply to Cape Verde, further confirming that Cape Verde does not fit the pattern of most dollarizing countries.